Torsional behavior of steel fiber reinforced concrete beams under combined torsion-bending-shear - Avinash, S. Pant; Suresh, R. Parekar (Journal of Structural Engineering, 2025)
An experimental investigation is carried out to assess the torsional behavior of steel fiber reinforced concrete (SFRC) rectangular beams, with longitudinal and web reinforcement, subjected to combined torsion-bending-shear. The tests were conducted on twenty samples of prototype and studied for their torsional resistance for combined loading under torsion-bending-shear. For all these beams, all the parameters were maintained identical except the three chosen parameters viz. torsion to moment ratio (T/M), torsion to shear ratio (T/V) and percentage of web reinforcement. The values of aspect ratio and volume fraction of fibers were kept uniform to 60 and 0.6% respectively for all the beams. The study involved the influence of web reinforcement on the ultimate torsional strength of SFRC beams under variable values of T/M and T/V ratios. The test results are compared with proposed model.